2002
DOI: 10.1271/bbb.66.73
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Expression for the Oxidation of Linoleic and Arachidonic Acid Esters in Their Mixed System

Abstract: Two polyunsaturated fatty acids (PUFAs) or their esters were mixed, and their oxidation processes were measured at 659 C and ca. 0% relative humidity. Except when a PUFA ester was mixed with a free PUFA, the oxidation of the less-oxidative PUFA was promoted as its content in the mixture decreased, while the oxidation of the more-oxidative PUFA was delayed with a decrease in its content. A kinetic model is proposed whereby a PUFA acts as the diluent for another PUFA, and the oxidation rate of the PUFA is propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…This dependency is reasonable because the rate expression of the autocatalytic type is derived based on the Two PUFAs or their esters were mixed, and their oxidation processes were observed [12]. The oxidation of the less-oxidative PUFA was promoted as its content in the mixture decreased, while the oxidation of the moreoxidative PUFA was delayed with a decrease in its content.…”
mentioning
confidence: 72%
“…This dependency is reasonable because the rate expression of the autocatalytic type is derived based on the Two PUFAs or their esters were mixed, and their oxidation processes were observed [12]. The oxidation of the less-oxidative PUFA was promoted as its content in the mixture decreased, while the oxidation of the moreoxidative PUFA was delayed with a decrease in its content.…”
mentioning
confidence: 72%
“…We have proposed the rate equations for the oxidation of two PUFAs, A and B, in their mixed system under the assumption that the oxidation rate of component i (i=A or B) is proportional to both the concentration of the unoxidized substrate i and the sum of the concentrations of oxidized A and B (Ishido et al, 2002):…”
Section: Resultsmentioning
confidence: 99%
“…However, the edible oil is a mixture of acylglycerols consisting of a variety of saturated and unsaturated fatty acids. Therefore, we measured the oxidation processes of a PUFA or its ester in the presence of a saturated fatty acid or its methyl ester (Ishido et al, 2001), and those of PUFAs in a system where two PUFAs or their esters coexisted (Ishido et al, 2002).…”
mentioning
confidence: 99%
“…We reported that the presence of saturated or unsaturated fatty acid also affected the oxidation of an unsaturated fatty acid. Addition of a saturated fatty acid of the free or ester form to an unsaturated fatty acid or its ester (substrate) retarded the oxidation of the substrate because the saturated fatty acid or the ester acted as a diluent to decrease the concentration of the substrate [4][5][6]. The dilution effect of a saturated lipid on the unsaturated one occurred in an oil-in-water emulsion system where droplets of the unsaturated lipid were covered with an emulsifier, the hydrophobic moiety of which was a saturated acyl group [7].…”
Section: Introductionmentioning
confidence: 99%
“…The dilution effect of a saturated lipid on the unsaturated one occurred in an oil-in-water emulsion system where droplets of the unsaturated lipid were covered with an emulsifier, the hydrophobic moiety of which was a saturated acyl group [7]. The kinetics for the oxidation of an unsaturated lipid mixed with a saturated lipid was analyzed [4][5][6] based on the kinetic equation of the autocatalytic type [8][9][10].…”
Section: Introductionmentioning
confidence: 99%